Sejarah Perkembangan Kajian Hadis di Turki: History of the Development of Hadith Studies in Turkey - Nayla Syifa'un Najmi; Musta'am, Zahrotal Kamilia; Samsuri, Samrotul Jannah; Muhid, Muhid (Pusat Penelitian dan Pengabdian masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2025)
This research explores the development of Hadith studies in Turkey over time and analyzes the role of educational institutions in enhancing the quality of Hadith scholarship. It also aims to identify the unique characteristics of Hadith studies in Turkey compared to those in other countries. The focus of this study includes identifying significant events in the history of Islam in Turkey, analyzing the evolution of Hadith studies throughout different historical periods, and examining the distinct features of Hadith scholarship in Turkey compared to other regions, especially the Middle East. Data were collected through an analysis of relevant literature sources, including books, journal articles, academic papers, and theses that discuss the development of Hadith studies in Turkey. The findings reveal that Hadith studies in Turkey have evolved from the Ottoman era to the modern period, characterized by a blend of classical scholarly traditions and Sufism. Despite the influence of modernization and secularization in the 20th century, educational institutions in Turkey have successfully maintained the continuity of Hadith studies, making it distinct from Hadith scholarship in the Middle East. This research contributes by providing new insights into the development of Hadith studies in Turkey, which has been underexplored in Indonesia. Additionally, it enriches the literature on the history and tradition of Hadith scholarship beyond the Middle East and identifies factors that contribute to the unique characteristics of Hadith studies in Turkey.